PENGARUH FOREIGN DIRECT INVESTMENT TERHADAP PEREKONOMIAN MASYARAKAT DUMAI PASCA BERLAKUNYA MASYARKAT EKONOMI ASEAN - Rachmat Kurniawan; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describes the strategy of Government of Dumai City toward an Asean Economic Community in 2012-2015. Asean Economic Community are held by Asean Member state toward a China, India and Japan economic growth. In order that Asean Economic community make a common market to integrated the market in Asean and it will be power to support the economic growth of Asean members.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the strategy of Government of Dumai City toward an Asean Economic Community. The theories applied in this research are Neo liberalism perspective with the Foreign direct investment.The research shows that strategy of Government of Dumai City toward an Asean Economic Community are built in economic and infrastructure. Some of policies are Government of Dumai are increase of foregin invest in Dumai City, create a some regulations in investment trade, increase a growth of infrastructure and Government of Dumai city had implemented of creative economi by saving model in everysubdistrict in Dumai City.Key words : Foreign Direct Investment (FDI), Dumai, economic community